The commodification of education and inequality in Indonesia: A sociological perspective - Sari, Kurnia Asni; Fajriani, Suci Wahyu; Gunawan, Gunawan; Zulqoifah, Ainul; Hartani, Mallia (Priviet Social Sciences Journal, 2025)
This study analyzes the phenomena of commodification and inequality in the Indonesian education industry from a critical sociological perspective. Education, which is a basic right for all citizens, has been transformed into a commercial commodity accessible only to groups with certain economic, social, and cultural capital. This study used qualitative methods with content analysis based on Bourdieu's capital theory and Weber's stratification. The results indicate that commodification of education through superior private schools, tutoring, and achievement pathways strengthens student privilege and widens the gap between social classes. The privatization of education obscures the principle of meritocracy and creates a cycle of structural injustice that ultimately makes it difficult for students to achieve vertical social mobility. This research finds that educational inequality in Indonesia is not only a matter of access but also a structural problem that is supported by an unequal social, cultural, and economic system.